What Led to Their Involvement in Litigation? — Missionaries as defendants in modern consular courts - ZHANG, Xiaoyu (Journal of Research for Christianity in China (JRCC), 2025)
Neither traditional Chinese legal history nor Chinese Christian history research has ever examined the status and role of missionaries in consular courts. In reality, many missionaries faced legal challenges: some were sued by Chinese citizens over missionary incidents, such as the Wushan Mission Incident; others encountered legal troubles due to publishing newspapers or writing articles, like the Li Jiabai vs. Qin De defamation case; and some even appeared in secular courts over internal church disputes, exemplified by the Fei Qihong vs. Fan John case. Thanks to the rich and detailed judicial archives of consular courts and contemporary accounts, we can reconstruct these cases in detail, revealing why missionaries, as emissaries of God, found themselves in secular courts, and examining the close relationship between consular jurisdiction and legal reforms in modern China. This also reminds us that research on missionaries and modern Chinese law should not focus solely on the influence of missionary translations on China's legal reforms. We must also explore the role missionaries played in secular legal life and understand the specific differences between their discourses and practices.
Keywords: Missionary Consular Jurisdiction Defendant Missionary Incident